2017
DOI: 10.31938/jsn.v3i1.52
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH KONSENTRASI Na2CO3 TERHADAP RENDEMEN NATRIUM ALGINAT DAN KANDUNGAN PROKSIMAT ALGINAT DARI RUMPUT LAUT Sargassum sp.

Abstract: Effect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
2
3
2
1
Order By: Relevance
“…In this study, the protein content of alginate produced from Sargassum sp was 0.76 + 0.064 %, which was comparable to the protein content of commercial alginate, i.e., 0.768% [37]. Those values were in the range of standard protein content as set by Committee on Codex Specifications [31], i.e., 0 -1%.…”
Section: Protein Contentsupporting
confidence: 63%
See 3 more Smart Citations
“…In this study, the protein content of alginate produced from Sargassum sp was 0.76 + 0.064 %, which was comparable to the protein content of commercial alginate, i.e., 0.768% [37]. Those values were in the range of standard protein content as set by Committee on Codex Specifications [31], i.e., 0 -1%.…”
Section: Protein Contentsupporting
confidence: 63%
“…Another study revealed that the moisture content of alginate extracted from Sargassum sp was (9,86 ± 0,04 %) -(13,74 ± 0,03 %) [4]. While moisture contents of commercial alginate [37] and alginate extracted [32] were 11.14 % and 11,27 %, respectively, which were also lower than that of alginate from this study. Alginate extraction [27] using Sargassum sp from Jogjakarta, Lampung, and Banten produced products with a moisture content of 9.99%, 11.75%, and 16.23%, respectively.…”
Section: Moisture Contentcontrasting
confidence: 53%
See 2 more Smart Citations
“…Menurut Srikandi et al, (2013) selisih nilai kadar karbohidrat sebelum ekstraksi (rumput laut coklat sebesar 19,06) dan sesudah ekstraksi (Na-alginat antar 4,40-5,94%) menunjukan perbedaan, hal ini disebabkan terpecahnya karbohidrat menjadi glukosa dalam perlakuan asam dan pemanasan, monosakarida yang larut tersaring pada saat pemisahan asam alginat yang diambil residunya yang mengakibatkan rendahnya kadar kabohidrat yang diperoleh. Dari uji kadar karbohidrat diatas hasil terbaik adalah Na-alginat dari Lampung dengan kadar karbohidrat sebesar 5.94% ± 2.35.…”
Section: Gambar 10 Rata-rata Hasil Uji Kadar Karbohidratunclassified